THE PARENTS ROLE - Apri Utami Parta Santi; Windy Atika Sani (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2017)
Abstract This study aims to prove that there is an influence between the role of parents to the attitude of religious children in the family environment. This research uses quantitative method which take sample of non probality sampling that is purposive sampling. Data collection techniques using questionnaires. Data analysis using statistic approach to item about validity and reliability used is Pearson correlation test with 0.5% significance level (5%) with total sample 40 respondents. Based on the calculation of rxy calculation of 0.655, it can be concluded that the role of parents have a very strong influence on the attitude of religious and direction of the influence of the role of parents to religious attitudes have the following regression equation Å¶ = 3.309 + 0.814X this is evidenced by the significance test using the -F test of the calculation results obtained Fhitung amounted to 0.1009 and Ftable of 4.12 while the contribution of the parent role to religious attitudes of 41.4% through the calculation of the coefficient of determination. The results of this study indicate that there is a significant or significant influence between the role of parents to religious attitudes.